ANTECEDENTS OF PRIVATE LABEL ATTITUDE AND PREFERENCE OVER NATIONAL BRANDS - Singh, Ajay; Gupta, Rahul; Kumar, Amol (International Journal of Supply Chain Management, 2018)
Abstract-Retail is one of the most dynamic and fast paced sectors in India. The Growth of the organized retail sector has led to the growth of the Private label brands in India. Private labels offer advantages to both the consumers and retailers. Retailers make huge margin of profit on private labels in comparison to National brand. Various factors are responsible for framing an attitude towards both the private labels and the National brands. Present study sets out to study customer s attitude and preference pattern with respect to different attributes such as-Demographics, Social factors, psychological factors. The study will ultimately assist the retailers in developing and implementing effective marketing efforts in respect of their brands. Keywords- Smart purchases, Value consciousness, perceived quality, Private label, Consumer attitude